2018
DOI: 10.1089/pop.2017.0164
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Camden Coalition of Healthcare Providers' First Medicaid Shared Savings Performance Evaluation

Abstract: Accountable Care Organizations (ACOs) aim to reduce health care costs while improving patient outcomes. Camden Coalition of Healthcare Providers' (Camden Coalition) work already aligned with this aim before receiving state approval to operate a certified Medicaid ACO in New Jersey. Upon its formation, the Camden Coalition ACO partnered with UnitedHealthcare and, through state legislation, Rutgers Center for State Health Policy (CSHP) was established as its external evaluator. In evaluating the Camden Coalition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In two‐sided risk models, the ACO may receive a greater portion of any savings, but it also must pay Medicaid if the total costs of care for their attributed patients exceed specific targets. Cost targets are usually predicted spending based on historical trends and population characteristics …”
mentioning
confidence: 99%
“…In two‐sided risk models, the ACO may receive a greater portion of any savings, but it also must pay Medicaid if the total costs of care for their attributed patients exceed specific targets. Cost targets are usually predicted spending based on historical trends and population characteristics …”
mentioning
confidence: 99%
“…Recalibration of models to include factors important for children, such as geography or PMCA score, as well as consideration of unique pediatric conditions or settings (eg, home care, pediatric intensive care) could impact pediatric ACO benchmarks. Additionally, exclusion thresholds for high-cost outliers, such as unpredictable catastrophic expenses, can impact ACO success . While it has been suggested that children with complex conditions be excluded from ACO responsibility, factors such as home-based care or prescription drug costs could add nuance when determining exclusion thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exclusion thresholds for high-cost outliers, such as unpredictable catastrophic expenses, can impact ACO success. 37 , 38 While it has been suggested that children with complex conditions 9 , 20 be excluded from ACO responsibility, factors such as home-based care or prescription drug costs could add nuance when determining exclusion thresholds. While MSSP ACOs exclude the top 1% of patients nationally by eligibility category, there are no guidelines for outlier exclusion in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…Regional Health Hubs have been successful in engaging various stakeholders and convening coalitions and programs to address long-term health conditions. [13][14][15][16] We present a case study of community and clinical care integration through the experience of a multi-faceted, community-based initiative in Trenton, NJ, focused on supporting patients with diabetes and barriers they are facing.…”
Section: Introductionmentioning
confidence: 99%